2015
DOI: 10.1088/1748-9326/10/3/034017
|View full text |Cite
|
Sign up to set email alerts
|

Cropland/pastureland dynamics and the slowdown of deforestation in Latin America

Abstract: Latin America has the planet's largest land reserves for agriculture and had the most rapid agricultural expansion during the twenty-first century. A large portion of the expansion replaced forests, as shown by many local and regional studies. However, expansion varied regionally and also replaced other land covers. Further, it is important to distinguish between changes in cropland and pastureland as they produce food at different levels of efficiency and intensity. We used thirteen years (2001)(2002)(2003)(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
124
0
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(149 citation statements)
references
References 70 publications
5
124
0
11
Order By: Relevance
“…The themes covered and sensors used in the four studies that concluded no improvement upon data fusion were varied, ranging from mapping crop lands, degraded savannah and forests and using Landsat, ASTER, IRS-1C, SPOT, ALOS PALSAR, RADARSAT and ERS. Three of these studies (ID 4,31,38) used data from segmented land boundaries during analysis (done by only 15 of the whole sample of 50 land use-related studies, Table 5), performed fusion prior to data analysis (Table 7) and mapped continuous land use variables. In contrast, eight other studies also performed segmentation and fused data prior to classification (ID 3,11,13,17,26,29,37,45) and found an improvement in results using data fusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The themes covered and sensors used in the four studies that concluded no improvement upon data fusion were varied, ranging from mapping crop lands, degraded savannah and forests and using Landsat, ASTER, IRS-1C, SPOT, ALOS PALSAR, RADARSAT and ERS. Three of these studies (ID 4,31,38) used data from segmented land boundaries during analysis (done by only 15 of the whole sample of 50 land use-related studies, Table 5), performed fusion prior to data analysis (Table 7) and mapped continuous land use variables. In contrast, eight other studies also performed segmentation and fused data prior to classification (ID 3,11,13,17,26,29,37,45) and found an improvement in results using data fusion.…”
Section: Discussionmentioning
confidence: 99%
“…[30]) (Figure 1) potentially stand to gain most from the integration of optical and radar data. For example, a major current concern raised in the land systems literature today is understanding specific land use trajectories of different commodity crops, i.e., the share of deforestation caused or the sources of land for different crop types [37][38][39]. Improved ability to differentiate specific crops within broad crop land classes would strongly benefit this research, allowing understanding the complex linkages between different commodities and targeting interventions to improve the sustainability of commodity-specific supply chains [40,41].…”
Section: Land Covermentioning
confidence: 99%
See 1 more Smart Citation
“…This involves both conversion of natural habitats to grassland and grazing and conversion to arable land to produce grain and soya for livestock consumption. De Sy and colleagues (67) estimate that~71% of rainforest conversion in South America has been for cattle ranching and a further~14% for commercial cropping, including soya for animal feed (pastureland is often subsequently converted to cropland) (68). In the past 20 years, exports of soya from South America to China (and other countries) have increased dramatically and now constitute one of the largest international commodity flows (Fig.…”
Section: Effects On the Environmentmentioning
confidence: 99%
“…More than 80% of the agricultural expansion that occurred in tropical regions over 1980-2000 came at the expense of forests [4]. In 2000-2010, a large part of agricultural expansion in Latin America occurred in forests [5]. Inversely, the abandonment of agricultural lands may lead to reforestation through natural regeneration and/or tree planting, a common phenomenon in Central America in recent decades [6][7][8].…”
Section: Introductionmentioning
confidence: 99%